KOMUNITAS ZOOPLANKTON DI PERAIRAN WADUK KRENCENG, CILEGON, BANTEN - Handayani, Sri; Patria, Mufti P (UI Scholars Hub, 2005)
Zooplankton communities in the Krenceng Reservoair, Cilegon, Banten. This research was carried out to know the structure of zooplankton communities and relations between the phytoplankton and zooplankton in the Krenceng Reservoair, Cilegon. The zooplankton abundance with used Sedwigck Rafter Counting Method, diversity and evenness were counted. Relations between zooplankton and the environmental factors as well as its relations to phytoplankton calculated with regression. The results showed that are 13 species of the zooplankton found which including in three classes with the highest abundance on Novembers 2002 and March 2003 of the Rotifera. The analysis of regression pointed out that the environmental factors such: pH, BOD5, nitrate, CO2 and abundance of phytoplankton influence the abundance zooplankton in November. While in March, the abundance of zooplankton is influenced by brigthtness, nitrate, orthophosphates and C organic. The abundance of phytoplankton influenced positively by the abundance of zooplankton